2020
DOI: 10.1007/s11469-020-00434-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Future Time Perspective, Body Awareness, and Social Connectedness in the Relationship Between Self-efficacy and Resilience

Abstract: Defined as the successful adaptation to dynamic environments, resilience is considered a cornerstone of mental health. However, with the underpinnings of resilience not yet fully understood, this manuscript tests the potential contribution of self-efficacy and embeddedness on resilience (explored through validated measures of future time perspective, body awareness, and social connectedness). The convenience sample of 18-to-77-year-old adults included 297 individuals, of which 36 were men and 171 were female. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…In contrast, Present Hedonistic and Future time perspectives were positively related to resilience. These outcomes are in line with previous findings confirming the existence of, among other things, a negative correlation between PN and resilience [10] and a positive relationship between resilience and FTP [11]. Our findings are also supported by previous outcomes which indicated Past Negative and Present Fatalistic perspectives as predictors of maladaptive functioning.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, Present Hedonistic and Future time perspectives were positively related to resilience. These outcomes are in line with previous findings confirming the existence of, among other things, a negative correlation between PN and resilience [10] and a positive relationship between resilience and FTP [11]. Our findings are also supported by previous outcomes which indicated Past Negative and Present Fatalistic perspectives as predictors of maladaptive functioning.…”
Section: Discussionsupporting
confidence: 93%
“…Individuals with a high level of FTP display a low level of ego-undercontrol, impulsive behavior, and sensation seeking. For example, FTP was positively correlated with resilience [11] and health responsibility [54]. Boyd and Zimbardo [58] claim that there should be a healthy balance between past, present, and future orientations.…”
Section: Theoretical Conceptualization Of Time Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“… Chittaro and Vianello (2013) reported that the past-negative time perspective and the present-fatalistic time perspective were associated with problematic online behaviors. More recently, O'Neill et al (2020) found that FTP was related with individual psychological resilience, which was viewed as the core component of mental health, and Sobol et al (2020) observed that optimistic attitudes that involve present orientation or future orientation are conducive to compliance with public health regulations during the COVID-19 pandemic.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Several studies demonstrated that time perspective is an important psychological variable associated with many areas of human functioning (i.e., well-being, health behaviors, risky behaviors) ( 92 94 ). More recently, O'Neill et al ( 95 ) also found that FTP is related with psychological resilience, intended as a core component of mental health. Particularly for young adults, planning for the future represents an important developmental task that becomes fundamental in order to orient and guide the students in their career decision-making ( 96 98 ).…”
Section: Discussionmentioning
confidence: 99%